2022
DOI: 10.1177/02692163221122325
|View full text |Cite
|
Sign up to set email alerts
|

The health of mothers of children with a life-limiting condition: A qualitative interview study

Abstract: Background: The number of children with a life-limiting condition is increasing. The mothers of these children commonly provide extensive care at home for their child and are at a higher risk of poor health than other mothers. The impact of this is rarely explored from mothers’ perspectives. Aim: To explore mothers’ accounts of their physical and mental health, experiences of accessing healthcare and who they think should support their health. Design: Qualitative semi-structured interviews were conducted and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 23 publications
4
18
0
Order By: Relevance
“…This is appropriate given that the secondary analysis relates to, as the primary analyses did, the health experiences and support needs of parents and that the same authors conducted the data collection and analysis. 12…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is appropriate given that the secondary analysis relates to, as the primary analyses did, the health experiences and support needs of parents and that the same authors conducted the data collection and analysis. 12…”
Section: Methodsmentioning
confidence: 99%
“…did, the health experiences and support needs of parents and that the same authors conducted the data collection and analysis. 12 Data were mapped onto the existing domains of the CSNAT (Paediatric) according to latent and semantic meaning. Data that did not relate directly to the domains within the CSNAT (Paediatric) were categorised separately.…”
Section: Secondary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…63 Similarly there is an increasing body of evidence on the physical, emotional and financial impacts on parents caring for a young person with a life-limiting condition, both during their life and in bereavement. [64][65][66] It is essential to consider the psychological and practical needs of the family and carers. For younger patients, support for siblings is also important, acknowledging their oftenunrecognised role as carers as well as their need for psychological support.…”
Section: Relief Of Caregiver Strainmentioning
confidence: 99%
“…In addition, parents report increased financial costs (Brandt et al, 2022), strain on relationships (Krantz et al, 2022; Postavaru et al, 2020) and various emotions, such as uncertainty, chaos, sadness, loneliness and grief (Bally et al, 2018). It has also been found that parents express grieving throughout the trajectory of their child's disease, especially at the time of diagnosis and when the child progressively loses functions (Fisher et al, 2022; Price et al, 2022). The grief is commonly referred to as ‘anticipatory grief reactions.’ This term describes persons going through grief reactions prematurely and detaching themselves under the threat of death (Lindemann, 1994).…”
Section: Introductionmentioning
confidence: 99%